Resilience factors in teachers of a communitary day care relating with the situations of social vulnerability - Rosa, Simone Brouwenstyn da; Romani, Patrícia Fasolo (Revista de Psicologia da IMED, 2015)
The objective of this study was to identify resilience factors involved in the processes of care and attention to children in a communitary day care in the metropolitan region of Porto Alegre, in the face of situations of social vulnerability. As results from the speech of the three participants, through semi-structured interviews, we highlight the positive emotional coping strategies. Considering the environment where the children and the teachers live, as well as the contact with another institutions to ensure that the rights of minors are primed and fulfilled. Therefore, the work of these educators are guided by stimulating health, physical and psychic. In conclusion, Despite the personal, social and professional difficulties, the participants demonstrated through the coping strategies they use, that they are resilient.